THE IMPACT OF BALANCED SCORECARD IMPLEMENTATION ON PERFORMANCE IN MANUFACTURING AND SERVICE SECTORS: A SYSTEMATIC LITERATURE REVIEW (2019–2024) - Shafira Widya Ramadhanti; Sopiah; Arief Noviarakhman Zagladi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the impact of Balanced Scorecard (BSC) implementation on organizational performance in manufacturing and service sectors through a Systematic Literature Review (SLR). The study adopts the PRISMA framework to systematically identify, screen, and analyze relevant literature published between 2019 and 2024. A total of 31 empirical articles were selected from reputable databases such as Scopus, Emerald Insight, and ScienceDirect. The findings indicate that the Balanced Scorecard is an effective strategic management tool that enhances organizational performance by integrating financial and non-financial perspectives, including customer satisfaction, internal processes, and learning and growth. In the manufacturing sector, BSC improves operational efficiency, productivity, and product quality, while in the service sector it strengthens customer satisfaction, transparency, and employee engagement. However, several challenges remain, such as limited managerial support, weak integration across perspectives, and insufficient focus on learning and growth dimensions. This study contributes by providing comprehensive insights into best practices, implementation challenges, and research gaps, as well as offering recommendations for future studies to develop sector-specific performance indicators and explore long-term impacts of BSC implementation.